Efektivitas Enhancer Natrium Lauril Sulfat Dalam Patch Topikal Antiinflamasi Ekstrak Etanol Kencur (Kaemferia Galanga L.) Terhadap Jumlah Neutrofil dan Makrofag Pada Mencit - Fatmawati, Desy; Dermayati, Cyntia Zain; Hamid, Iwan Sahrial; Hendriati, Lucia (Indonesian Research Gateway)
Ethanol extract Kencur (Kaempferia galanga L.) has been proven to have antiinflammatory effect as well as to decrease the side effect of NSAIDs drug use, to develop the formulation of ethanol extract of kencur, then made in the dosage form of topical patch. Topical patch preparations are expected to avoid effects on the gastrointestinal tract, first- pass metabolism, and facilitate the use of the patient thereby increasing patient compliance. In the patch formulation, the most important things to note is the penetration enhancer/ enhancer, and enhancer used in this study is sodium lauryl sulphate. This study aims to determine the effectiveness of sodium lauryl sulphate in the preparation of a topical patch of kencur extract as anti inflammatory on the number of neutrophils in the blood. The research method uses canrrageenan as an inflammation inductor and neutrophil count observation was conducted using blood smears, then was observed on the first, third and seventh. Group of treatment which was given sodium diclofenac gel as positive control, group of treatment which was without enhancer as the 1st group, groups of treatment which were givenenhancer 1%, 3%, and 5% as the 2nd, 3rd and 4th group. The result was analyzed by one way ANOVA, followed by Post Hoc Duncan. The experimental results prove that there was a significant difference between the number of neutrophils and macrophages in the negative control group who were not given enhancer and the treatment group were given enhancer sodium lauryl sulphate values ( p < 0.05 ). As well as the group treated with the addition of enhancer sodium lauryl sulfate showed a greater amount of decline compared to the treatment group that contains only ethanol extract kencur.